2006
DOI: 10.1097/01.prs.0000209392.85221.0b
|View full text |Cite
|
Sign up to set email alerts
|

Management of Mandible Fractures

Abstract: The authors review the diagnosis and current trends in management of mandible fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 52 publications
1
75
0
3
Order By: Relevance
“…12,23,24,25 Many authors reported the angle as the most frequently affected site, 4,6,13,24 whereas others reported this to be the mandible body 5,10,20 and symphysis. 4,22 In this sample, the condyle was the most frequently affected site (28%).…”
Section: Discussionmentioning
confidence: 97%
“…12,23,24,25 Many authors reported the angle as the most frequently affected site, 4,6,13,24 whereas others reported this to be the mandible body 5,10,20 and symphysis. 4,22 In this sample, the condyle was the most frequently affected site (28%).…”
Section: Discussionmentioning
confidence: 97%
“…18,19 The fractures of the mandibular condyle are better appreciated in sagittal plane, while 3-D reconstructions ( Figure 3) are extremely useful in planning surgical management. [18][19][20] The sensitivity of multidetector computed tomography (MDCT) to detect mandibular fracture are 100% whereas orthopanoramic radiograph and conventional x-rays had only 86% sensitivity. 16 Multidetector computed tomography (MDCT) is the investigation of choice and is the most appropriate imaging modality to evaluate patients of maxillofacial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Complications that may arise as a result of mandible fracture repair include wound infection, malocclusion, nonunion, malunion, tooth loss, trismus, ankylosis, deviation, scars, paraesthesias, failed procedures, re-operation, hardware removal, chronic pain and functional deficit. [25][26][27][28] It also causes significant economic expense secondary to procedural costs and patient time off work and associated income loss. The association between reduced quality of life and facial trauma is well known.…”
Section: Discussionmentioning
confidence: 99%